Detailed modeling of large scale photovoltaic power plants under partial shading conditions. (December 2019) - Robles–Campos, Héctor R.; Azuaje–Berbecí, Bernardo J.; Scheller, Christopher J.; Angulo, Alejandro; Mancilla–David, Fernando
Highlights: Electro–thermal modular model of PV cells and BPDs depicted by an equivalent circuit. A thermal equation that yields the BPD junction temperature, including heat transfer. Comparison of several MPPT algorithms, using our model, operating under PS conditions. Abstract: As the popularity of solar panels increases, significant research is being performed on maximizing the power extracted from photovoltaic systems. A phenomenon known as partial shading is a major source of power losses for photovoltaic plants. One way to reduce the effects of partial shading conditions is by using bypass–diodes. Typically any number of series and parallel–connected photovoltaic cells, known as photovoltaic cell arrays, are connected in anti–parallel with bypass–diodes. Due to this, it is advantageous to have an equivalent model for a photovoltaic cell array that is connected to bypass–diodes. In order to accurately develop this model, it is necessary to consider both series and parallel configurations of bypass–diodes, as well as the thermal behavior of bypass–diodes. The bypass–diode's temperature model must be comprised of the constantly changing dissipated power, the effects of wind speed and the ambient temperature. This paper constructs an electro–thermal modular model for any size photovoltaic system and includes the effects of both the photovoltaic cells and bypass–diodes. A detailed analysis of the proposed model is performed and is then validated in both PSCAD/EMTDC and Matlab–Simscape. The proposed model is then further validated by the use of real measurements of ambient temperature, cell temperature, wind speed and then finally by a performance analysis of several maximum–power–point–tracking algorithms.